Retrospective assessment of the use of extended-release cabergoline in the management of equine pituitary pars intermedia dysfunction - Sundra, Tania; Kelty, Erin; Rossi, Gabriele; Rendle, David (Frontiers in Veterinary Science, 2024)
Dopaminergic agonists are accepted as the most effective treatment for pituitary pars intermedia dysfunction. However, some horses are refractory to daily oral pergolide, the recommended registered treatment. Extended-release cabergoline (ERC) injection may offer an alternative. The objective of this retrospective case series was to describe clinical and endocrinological responses to ERC. Medical records of horses treated with weekly intramuscular injections of ERC (5mg/ml, BOVA Aus) at either 0.01mg/kg (high dose, HD) (n=10) or 0.005mg/kg (low dose, LD) (n=30) were reviewed. Short-term ACTH responses were assessed at 5-8 days using a Wilcoxon signed ranked test. Longer-term ACTH responses (30 to 365 days) were assessed using generalised estimating equations. Five to eight days after the first dose of LDERC, median adrenocorticotropic hormone (ACTH) concentration was lower (p=0.001), changing from 153pg/ml (IQR: 78, 331) to 57pg/ml (IQR: 30, 102). With HDERC, median ACTH concentration was also 153pg/ml (IQR: 96, 185) before and then 56pg/ml (IQR: 29, 86) after 5-8 days of treatment (p=0.047). Over 12-months of treatment, ACTH concentration ranged from 14 to >1250pg/ml (median: 51pg/ml) in horses treated with LDERC and 20 to 472pg/ml (median: 50pg/ml) in horses treated with HDERC. Measurements remained above the seasonal reference range in 39.3% and 52.3% of horses treated with LDERC and HDERC, respectively. Clinical improvement was reported by owners in 78.3% and 100% of horses treated with LDERC and HDERC, respectively. Partial, self-limiting inappetence was reported in 30.0% of LDERC and 60% HDERC cases. Seven horses exhibited lethargy (5 LDERC, 2 HDERC). Insulin concentrations measured 30 days post-ERC treatment were no different from baseline. Clinical and endocrinological responses were consistent with results of previous reports of oral pergolide treatment. Weekly injection of ERC may be an effective alternative to pergolide; the 0.005 mg/kg dose appeared to be as effective, with less risk of inappetence, than the 0.01mg/kg dose that has been reported previously.